Coupling Enhancement of a Flexible BiFeO3 Film-Based Nanogenerator for Simultaneously Scavenging Light and Vibration Energies - Han, Xiao; Ji, Yun; Wu, Li; Xia, Yanlong; Bowen, Chris R.; Yang, Ya (Nano-Micro Letters, 2022)
Coupled nanogenerators have been a research hotspot due to their ability to harvest a variety of forms of energy such as light, mechanical and thermal energy and achieve a stable direct current output. Ferroelectric films are frequently investigated for photovoltaic applications due to their unique photovoltaic properties and bandgap-independent photovoltage, while the flexoelectric effect is an electromechanical property commonly found in solid dielectrics. Here, we effectively construct a new form of coupled nanogenerator based on a flexible BiFeO3 ferroelectric film that combines both flexoelectric and photovoltaic effects to successfully harvest both light and vibration energies. This device converts an alternating current into a direct current and achieves a 6.2% charge enhancement and a 19.3% energy enhancement to achieve a multi-dimensional "1 + 1 > 2" coupling enhancement in terms of current, charge and energy. This work proposes a new approach to the coupling of multiple energy harvesting mechanisms in ferroelectric nanogenerators and provides a new strategy to enhance the transduction efficiency of flexible functional devices. Highlights: 1 Development of new form of coupled nanogenerators to enhance performance. 2 Energy in the form of light and vibration is successfully harvested, by converting an alternating current signal into a direct current signal. 3 New approach to creating coupled nanogenerators, where multiple harvesting mechanisms by exploiting ferroelectric materials are achieved.